Risks and environmental impacts of Kazakhstan’s uranium production - Sydykov Yerlan; Sailaubay Yerlan; Maslov Khalil; Zhanbossinova Albina (BIO Web of Conferences)
The article examines the establishment of uranium production in Kazakhstan and assesses the risks of man-made disasters and their consequences. The authors trace the history of the uranium industry and conduct a statistical analysis of uranium deposits based on their geographical distribution. The Republic of Kazakhstan holds a significant position in the global uranium market due to its substantial uranium reserves. While the country benefits from the presence of three unique industries – tantalum, uranium, and beryllium – these also pose certain risks. The article highlights the industrial disaster caused by a beryllium fire at the Ulba Metallurgical Plant and its environmental and public health consequences. The study further explores the development of Kazakhstan's nuclear industry, its integration into international uranium markets, and the establishment of the International Nuclear Fuel Bank in the country. Additionally, it provides an analysis of the environmental threats and risks associated with uranium production.